1836 Tenn. Comp. Stat. 100, Arms, 1821-Chapter 13, § 1 - (:unkn) unknown (My University, 1821)
§Every person so degrading himself by carrying a dirk, sword cane, Spanish stiletto, belt or pocket pistols, either public or private, shall pay a fine of five dollars for every such offence, which may be recovered by warrant before any justice of the peace, in the name of the county for its use, in which the offence may have been committed; and it shall be the duty of a justice to issue a warrant on the application, on oath, of any person applying; and it shall be the duty of every judge, justice of the peace, sheriff, coroner, and constable within this state, to see that this act shall have its full effect: Provided, that nothing herein contained shall affect any person that may be on a journey to any place out of his county or state.
Keywords: CARRY